An exploration of the efficacy of telehealth in the assessment and management of stress urinary incontinence among women in rural locations - Fary, Robyn; Conlan, Lee; Thompson, Judith (2016)
This case series aimed to investigate the impacts and acceptability of, as well as barriers to, physiotherapy assessment and treatment of six women with self-reported stress urinary incontinence, living in rural areas using telehealth technology. Women with selfreported urinary incontinence living in rural locations were recruited to receive an initial continence physiotherapy assessment and treatment session via telehealth. Severity of stress urinary incontinence, condition-specific quality of life and urinary leakage frequency were measured. Satisfaction with the telehealth assessment process and barriers to accessing skilled continence physiotherapists were also assessed. Six participants, aged 24-56 years, were determined to have moderate to severe stress urinary incontinence (range 6-17) at baseline, measured with the Modular Questionnaire-Urinary Incontinence Short Form. Six weeks following the intervention, all participants showed an improvement in urinary symptom scores, and four participants showed an improvement in quality of life and urinary leakage. Following intervention, all participants rated their condition as improved. There was high satisfaction with the telehealth method of delivery. The main barriers to access to a continence-trained physiotherapist were inconvenience and site-related factors. Initial assessment and management provided by a continence-trained physiotherapist via telehealth may be an effective solution to lack of access for women with stress urinary incontinence living in rural Australia.